Implementación de un sistema de medición mediante el método Scada para determinar pérdidas de carga lineales en tuberías de aceite - Benitez Zamora, Antonio Xavier (2022)
The inaccuracy in pressure and flow measurements in the experimental system in oil flow has limited the analysis and determination of the friction factor in pipes, due to the use of measuring devices that are not in accordance with the fluid flowing through the system. In this sense, three differential pressure sensors have been implemented with a measurement range from 0 to 40 Psi and a degree of accuracy of ± 0.5 %, a flow sensor with a range from 0.15 to 1.5 m^3/h and an error of ± 1 %, these were dimensioned for the fluid of the system. The objective of this work was to implement a measurement system through the SCADA method, which determines linear head losses in three different sections of galvanized steel pipes with diameters of 1'', 3/4'' and 1/2''. The design of the measurement system was carried out using Ignition software, allowing the interface with the PLC S7-1200 through OPC UA communication. Additionally, the comparison of the experimental and theoretical results of the linear head losses in nine data taken for section 1 (1'' pipe) showed an average error of 0.22 %, in section 2 (3/4'' pipe) an error of 1.32 % and in section 3 (1/2'' pipe) an error of 5.67 %, validating the experimental results. The estimated cost of the measurement system is $ 3663.5.